2016
DOI: 10.1148/radiol.2016164018
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cancer Detection Rate and Variations in the Recall Rate Resulting from Implementation of 3D Digital Breast Tomosynthesis into a Population-based Screening Program

Abstract: Purpose:To compare the recall and cancer detection rates (CDRs) at screening with digital breast tomosynthesis (DBT) with those at screening with two-dimensional (2D) mammography and to evaluate variations in the recall rate (RR) according to patient age, risk factors, and breast density and among individual radiologists at a single U.S. academic medical center. Materials and Methods:This institutional review board-approved, HIPAA-compliant prospective study with a retrospective cohort included 85 852 asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 12 publications
1
38
0
1
Order By: Relevance
“…The development of digital breast tomosynthesis (DBT), a pseudo-three-dimensional technique that minimizes the ambiguity of overlapping breast tissue (6), has decreased recall rates while increasing CDRs. When DBT is used in combination with digital mammography, studies have shown a 15%-40% decrease in recall rate (7)(8)(9)(10)(11)(12) and up to a 29% increase BREAST IMAGING: Screening Digital Mammography Recall Rate DiPrete et al separately analyzed. All six radiologists were fellowship-trained breast radiologists (including author A.P.L.)…”
Section: Implication For Patient Carementioning
confidence: 99%
“…The development of digital breast tomosynthesis (DBT), a pseudo-three-dimensional technique that minimizes the ambiguity of overlapping breast tissue (6), has decreased recall rates while increasing CDRs. When DBT is used in combination with digital mammography, studies have shown a 15%-40% decrease in recall rate (7)(8)(9)(10)(11)(12) and up to a 29% increase BREAST IMAGING: Screening Digital Mammography Recall Rate DiPrete et al separately analyzed. All six radiologists were fellowship-trained breast radiologists (including author A.P.L.)…”
Section: Implication For Patient Carementioning
confidence: 99%
“…1). Sixteen studies [12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] met our predefined inclusion criteria and were included in the evidence synthesis. The meta-analysis was performed separately for 5 diagnostic studies, and for 11 screening studies (these were examined separately for 8 screening studies that used two independent study groups, and the 3 screening studies that used one study group).…”
Section: Study Inclusionmentioning
confidence: 99%
“…All but two of 11 screening studies performed one screening round. Nine screening studies reported CDR [16,19,20,[23][24][25][26][27]29] and nine studies reported recall rate [16,19,20,22,24,[26][27][28][29].…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…A mammography population-based screening programme can also be successfully integrated in a midlower income country and continues to be the only evidence-based screening tool to reduce breast-cancer-specific mortality (29). Increase of incremental cancer detection rate (around 2/1000 examinations) and absolute decrease of recall rate (about 1-1.5%) have been observed after implementation of 3D digital breast tomosynthesis in population-based screening trials (30)(31)(32)(33). Many logistical issues and the role of potential over-diagnosis of DCIS need further evaluation to determine the potential implications and cost of supplemental HHUS, SAUS, combined 2D + supplemental 3D mammographic screening (30)(31)(32)(33)(34)(35)(36).…”
Section: Evidence Based Medicine and Coverage For Supplemental Screeningmentioning
confidence: 99%